Accesibilitatea serviciilor de învăţământ şi asistenţă medicală - dimensiune a calităţii vieţii - Novak, Andrei (Calitatea Vieții, 1992)
Tie accessibility of the above-mentioned services is approached from the viewpoint of some indicators defining the fair distribution of factors — which create the prerequisites — and, also, of those outlining the proper accessibility. The paper offers the computational algorithm of the indicator concerning the ensurance with human means (IARU ) and an application of it the field of health care.